Penguatan Struktur Tanah Melalui Penanaman Bambu di Yayasan Bambu Lingkungan Lestari dan Kehati Bajawa - Umbu A Hamakonda; Vinsensia Bure; Victoria Ayu Puspita; Igniosa Taus (BADAN PENERBIT STIEPARI PRESS, 2025)
Currently, the government is encouraging land conservation and land rehabilitation efforts, such as reforestation and reforestation. Intended to maintain soil fertility, restore critical land, and improve water management. To achieve this goal, damaged land can be repaired by preserving bamboo plants as reforestation and rehabilitation plants. By preserving bamboo, damaged land will function properly again in a relatively short time, so that natural resources of forests, land, and water can be utilized properly. The purpose of this community service is to strengthen the soil structure through bamboo planting in Ubedolumolo I Village, Bajawa District, Ngada Regency. The method of implementing this community service activity is a survey and direct planting in the field in several locations in Ubedolumolo I Village which has a land area for cultivating bamboo plants as an effort to preserve through land rehabilitation and soil conservation in the area around the springs and rivers of Ubedolumolo I Village. The results of community service show that planting bamboo can improve and strengthen the soil structure and increase water debit in the spring and river areas. The bamboo lestari foundation plays an active role in bamboo cultivation as an alternative to strengthening the soil structure to be better